Prevalence of Advanced HIV Disease, Cryptococcal Antigenemia, and Suboptimal Clinical Outcomes Among Those Enrolled in Care in Vietnam. (15th December 2021) - Dat, Vu Quoc; Lyss, Sheryl; Dung, Nguyen Thi Hoai; Hung, Le Manh; Pals, Sherri L.; Anh, Ho Thi Van; Kinh, Nguyen Van; Bateganya, Moses
Abstract : Background: People living with advanced HIV disease are at high risk of morbidity and mortality. We assessed the prevalence of cryptococcal antigenemia (CrAg) and clinical outcomes among patients newly presenting with CD4 ⩽100 cells/μL in Vietnam. Setting: Twenty-two public HIV clinics in Vietnam. Methods: During August 2015–March 2017, antiretroviral therapy (ART)-naïve adults presenting for care with CD4 ⩽100 cells/μL were screened for CrAg. Those who consented to study enrollment were followed up for up to 12 months and assessed for clinical outcomes. Results: Of 3504 patients with CD4 results, 1354 (38.6%) had CD4 ⩽100 cells/μL, of whom 1177 (86.9%) enrolled in the study. The median age was 35 years (interquartile range 30–40); 872 (74.1%) of them were men, and 892 (75.8%) had CD4 <50 cells/μL. Thirty-six patients (3.1%) were CrAg-positive. Overall, 1151 (97.8%) including all who were CrAg-positive initiated ART. Of 881 patients (76.5%) followed up for ≥12 months, 623 (70.7%) were still alive and on ART at 12 months, 54 (6.1%) had transferred to nonstudy clinics, 86 (9.8%) were lost to follow-up, and 104 (11.8%) had died. Among all 1177 study participants, 143 (12.1%) died, most of them (123, 86.0%) before or within 6 months of enrollment. Twenty-seven patients (18.9%) died of pulmonary tuberculosis, 23 (16.1%) died of extrapulmonary tuberculosis, 8 (5.6%) died of Talaromyces marneffei infection, and 6 (4.2%) died of opioid overdose. Eight deaths (5.8%) occurred among the 36 CrAg-positive individuals. Conclusions: Late presentation for HIV care was common. The high mortality after entry in care calls for strengthening of the management of advanced HIV disease.